Autophagy Dually Induced by AMP Surplus and Oxidative Stress Enhances Hemocyte Survival and Bactericidal Capacity via AMPK Pathway in Crassostrea hongkongensis - Dang, Xin; Wong, Nai-Kei; Xie, Yongli; Thiyagarajan, Vengatesen; Mao, Fan; Zhang, Xiangyu; Lin, Yue; Xiang, Zhiming; Li, Jun; Xiao, Shu; Noor, Zohaib; He, Yuanqiu; et al. (Frontiers in Cell and Developmental Biology, 2020)
Crassostrea hongkongensis (Hong Kong oyster) is an ecologically and economically valuable shellfish endemic to South/Southeast Asia. Due to ocean acidification and warming waters, they have become increasingly vulnerable to invading microbes including Vibrio parahaemolyticus, a significant foodborne human pathogen. In recent years, outbreaks of V. parahaemolyticus have emerged as a perennial phenomenon in parts of the world, necessitating to better understand the biology of host-pathogen interactions in this under-examined marine invertebrate. Although an immunologically relevant autophagy apparatus has been identified in Crassostrea gigas, an evolutionarily close mollusk cousin, the precise mechanistic details of C. hongkongensis autophagy during V. parahaemolyticus infection are still wanting. Here, we compellingly demonstrated that in vivo V. parahaemolyticus challenge robustly triggered autophagic signaling in C. hongkongensis hemocytes peaking at 6 h post-infection, which subsequently promoted bacterial clearance and dampened premature apoptosis. Simultaneously, a large surplus of adenosine monophosphate (AMP) and elevations in reactive oxygen species (ROS, specifically mitochondrial O2•- and cellular H2O2) formation were observed post-infection. Extrinsically applied AMP and ROS could synergistically induce AMP-activated protein kinase (AMPK) phosphorylation to stimulate downstream autophagic events. V. parahaemolyticus infection-induced autophagy was pharmacologically shown to be AMPK-dependent in vivo. Overall, our results establish autophagy as a crucial arm of host defense against Vibrio infections in mollusks, and provide new insights into the underappreciated roles of ROS and AMP as co-regulators of autophagy.